Technology Integration in Professional Education Courses: Utilizing the INTASC Principles - Saundra L. Wetig; Phyllis K. Adcock (Educational Considerations, 2004)
In response to emerging federal, state, and local standards, the University of Nebraska at Omaha through the Teacher Education Department strives to equip teacher candidates with the academic, social, as well as the technological skills needed in 21st century classrooms.